Holiday in the Sun - Steve Purcell; Ashley, Olsen; MaryKate Olsen (USA Dualstar Productions, 2001)
Whisked away to the Bahamas in a private jet by their pilot dad, Mary- Kate and Ashley Olsen (playing twins Alex and Madison) are initially disappointed to be missing their class trip to Hawaii. (Just what high school do these girls attend?) But the 15-year-olds recover upon meeting up with their mom on the sunny tarmac, checking into their own suite at the Atlantis resort, and getting acquainted with some cute boys on the island. Parents may see this 88- minute movie as one long advertisement for the Paradise Island resort, with the constant mentioning of its name and endless showcasing of its attractions. But kids, particularly girls ages 7 to 12, will get a kick out of Alex's rivalry with the rich superwitch Brianna for marine worker Jordan's affections. Then there's the updated Cyrano storyline with Dad's business partner's son Griffen coaching dim-but-likable Scott on how to win over Madison. Throw in an antiquities smuggling subplot, some dolphin hugging, horseback riding, and wave running and you've got some fairly innocent entertainment augmented with frothy tunes by teen group up-and-comers Play, Empty Trash (featuring vocals by the twins), Tte American Girls, and Noogie.
Brent Goldberg
Language : English
Subtitle : English
Keywords: Family